Mobilizing on the extreme right Germany, Italy, and the United States - Caiani, Manuela; Della Porta, Donatella, 1956-; Wagemann, Claudius (Oxford : Oxford University Press, 2012)
This volume compares the extreme right in Italy, Germany, and the United States using concepts and methods developed in social movement studies, paying particular attention to the discourses actions, and organisational structures of each movement.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Right-wing extremists -- Germany; Right-wing extremists -- Italy; Right-wing extremists -- United States